Treatment advances in antiphospholipid syndrome: 2022 update. (August 2022) - Erton, Zeynep Belce; Erkan, Doruk
Abstract: Antiphospholipid syndrome (APS) is a systemic autoimmune disorder characterized by thrombosis, pregnancy morbidity, or non-thrombotic manifestations in patients with persistently positive antiphospholipid antibodies (aPL). Conventional treatment strategies of antiphospholipid syndrome focuses on antithrombotic agents, however they are usually not effective for microvascular and non-thrombotic manifestations of aPL. In parallel to our increased understanding of the mechanisms of aPL-mediated clinical events, immunosuppression has been increasingly used in aPL-positive patients. This review focuses on the role of potential targeted immunosuppressive treatments in APS (B-cell inhibition, complement inhibition, mechanistic target of rapamycin inhibition, and traditional rheumatologic disease–modifying agents including hydroxychloroquine) and future perspectives.